Identitas Budaya Dalam Konteks Perubahan Sosial - Anisa Pebriani; Reni Kurnia Ramadhan; Aisyah Purwitasari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Cultural identity which is formed in life within a society can also influence the self-perception of each member within a society. Cultural identity in a context of social change is also a symptom where there is a social structural change in cultural patterns in a society with social changes which can cause a culture in Indonesia to experience a change in it. Cultural identity is also a characteristic which can connect a communication system, but with social change itself it can also make the change occur due to an essence or basic human nature of that society.